PERAMALAN EKSPOR LUAR NEGERI BANTEN MENGGUNAKAN MODEL ARIMAX - Saeful Hidayat; Nisrina Hakim (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
Forecasting Banten exports is one of the important elements for formulating economic growth targets in the development planning document prepared by the Banten Provincial Government. The purpose of this study is to forecast exports by utilizing export data from the BPS and the United States manufacturing purchasing managers index (PMI) which is derived from the Institute of Supply Management (ISM). The results showed that the ARIMAX model has a very good forecasting ability. This is indicated by the MAPE value which reached 8.84 percent. However, forecasting accuracy will decrease as the forecasting time span increases